2014
DOI: 10.1021/ma500839p
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dependence of the Molecular Mobility in the Amorphous Fractions of Polylactide

Abstract: Fragilityindex and cooperativity length characterizing the molecular mobility in the amorphous phase are for the first time calculated in drawn polylactide (PLA). The microstructure of the samples is investigated from wide-angle X-ray scattering (WAXS) whereas the amorphous phase dynamics are revealed from broadband dielectric spectroscopy (BDS) and temperature-modulated differential scanning calorimetry (TMDSC). The drawing processes induce the decrease of both cooperativity and fragility with the orientation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 91 publications
5
64
0
Order By: Relevance
“…Such behavior can be explained by a broader relaxation time distribution, i.e. an increasing heterogeneity of the molecular dynamics related in the glass transition process due to spatial composition heterogeneities [22,25,29]. 9 ± 2 nm [39]) and could be compared with the cooperativity lengths in the amorphous EVA copolymers (VAc content > 40 wt.%).…”
Section: Thermal Analysismentioning
confidence: 99%
“…Such behavior can be explained by a broader relaxation time distribution, i.e. an increasing heterogeneity of the molecular dynamics related in the glass transition process due to spatial composition heterogeneities [22,25,29]. 9 ± 2 nm [39]) and could be compared with the cooperativity lengths in the amorphous EVA copolymers (VAc content > 40 wt.%).…”
Section: Thermal Analysismentioning
confidence: 99%
“…They suggested that it constituted therefore an accelerated pathway for transport of penetrants around crystalline lamellae, counteracting the tortuosity increase occasioned by the same lamellae. Delpouve et al [25] worked on the cooperativity length and the fragility index of semicrystalline bi-axially stretched and post-stretching annealed PLA samples. They showed that the amorphous phase of the annealed samples had accelerated segmental motions, which would be beneficial for the gas permeability and not for the barrier properties.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the strong dependence of PLA macroscopic properties on its microstructure [15] and molecular dynamics [16], the cooperativity of the alpha relaxation process has been particularly investigated when the relaxation dynamics of the amorphous phase are modified by orientation [17], crystallization [13], or even plasticization [11]. However, the impact of several microstructural modifications on the amorphous phase dynamics remains unknown.…”
Section: Introductionmentioning
confidence: 99%